Mechanism for Distributing Uninhabitable Home Assistance in Cileunyi Kulon Village Siyasah Dusturiyah Perspective - Nadiya Sri Rahayu; Chaerul Shaleh; Lutfi Fahrul Rizal (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Poverty is often a serious discussion in overcoming it. The government has not found a glimmer of hope in overcoming poverty, even though the government continues to look for various ways so that poverty can be conquered. The purpose of this study is none other than to analyze how the mechanism of distribution of the uninhabitable house assistance program discusses the priority scale, benefits and review of siyasah dusturiyah in fulfilling the rights of the community in Cileunyi Kulon Village. One of the countermeasures carried out in Cileunyi Kulon Village is by running several assistance programs related to uninhabitable houses. With this program, it is hoped that it can be of benefit in the realm of society, and realize the government's desire to reduce poverty. Cileunyi Kulon Village has realized the uninhabitable house assistance program as one of the government's achievement targets in making the community prosperous, with the aim of maintaining human life in accordance with maqashid sharia, namely promoting maslahat, and leaving mudharat. The principle of siyasah dusturiyah which includes trust and justice makes how a leader exercises his power in accordance with Islamic law that refers to the Qur'an and Hadith. Therefore, the review of siyasah dusturiyah is used as an analysis knife in this research in Cileunyi Kulon Village because this research is considered in line with what is based on the principles of jurisdiction.